Celtuce — Lactuca sativa var. asparagina L. - James M. Stephens (EDIS)
This document describes Celtuce, also known as stem lettuce, celery lettuce, and asparagus lettuce. Celtuce is grown for its edible enlarged seed stalk, which resembles a cross between celery and lettuce. The outer leaves can be eaten young but become bitter quickly. The central stalk, when peeled, provides a soft, translucent green core that can be consumed fresh or cooked. Celtuce thrives in cool weather and should be planted in fall, winter, or early spring. It is rarely grown in Florida gardens but has shown promise in trials. Original publication date May 1994.